Manajemen Teknik Klinis terhadap Instrument Patah yang Tertinggal dalam Prosedur Perawatan Saluran Akar: A Literature Review - Zovai Hiskia Sianturi; Widi Prasetia (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The management of fractured endodontic instruments during root canal treatment represents a significant challenge in clinical endodontic practice. Instrument fracture can hinder effective cleaning and disinfection of the root canal system, increase the risk of complications, and potentially compromise treatment outcomes. Therefore, the selection of an appropriate management technique is crucial to ensure procedural success and to maintain a favorable prognosis for the treated tooth. This literature review aims to discuss and analyze various clinical techniques used in the management of fractured endodontic instruments. The methods reviewed include non-surgical retrieval techniques, ultrasonic activation, mechanical approaches using specialized auxiliary devices, and electrochemical dissolution methods. The selected articles consist of relevant case reports, retrospective studies, and clinical investigations, with particular emphasis on the effectiveness of each technique, clinical indications, and factors influencing the success of instrument retrieval. The results of this review indicate that non-surgical techniques are the most frequently employed approaches and demonstrate high success rates, especially when combined with ultrasonic devices and magnification aids. Ultrasonic techniques have been shown to be effective in improving accessibility and visualization of fractured instruments, thereby facilitating fragment removal while minimizing dentinal damage. Electrochemical dissolution methods have also been reported to be effective in certain clinical situations; however, their success rates vary depending on the type and material composition of the fractured instrument.